Representation of Islamic value in Verbal Communication of Ayat-Ayat Cinta Movie's Character - Achmad fasha Amarullah (LP2M Universitas Sarjanawiyata Tamansiswa, 2020)
Since at least 170 thousand years ago, humans have begun to use clothing and attach meaning to it. The contemporary socio-religious dynamics of the phenomenon brought back robes among people in Indonesia, especially men. The picture of the robes of the two cultures is analysed by looking at the icons, indexes, and symbols that make up the meaning of the robes. Culture itself is defined as a system of behaviour that is transmitted socially to the symbol as the highest cultural element. Many of them do not understand the basic principles of Islam itself, such as how Islam regulates the way of life between men and women. Their misunderstanding starts from their failure to understand the wrong concept which causes them to understand the wrong concept. correct understanding is needed to make things clear. The Qur'an has a certain section on matters of the lives of men and women. From the results of the analysis shows that the robe in Arabic means: shows the practical value of doing business, shows the Arabic rules over other nations, to build Arab unity, become a protective family, lead a relaxed life, simplicity, pattern, religiosity, conformity, social status, and worship. Comparison with the robes worn in Indonesia found that nine of these eleven meanings have shifted while two meanings: simplicity and worship, still remain the same as in Arabic, even stronger.